Phytochemical screening of Ayer Hitam Forest Reserve : Isolation of Ariskanin-A from Thottea corymbosa (Griff.) Ding Hou (Aristolochiaceae) - Yusoff, Nik Idris; Mat So'ad, Siti Zaiton; Suki, Ujang; Ibrahim, A. Zainuddin (Universiti Putra Malaysia Press, 2001)
During a phytochemical screening of higher plants at Ayer Hitam Forest Reserve, Puchong, Selangor, we collected a large amount of sample of Thottea corymbosa roots for further investigation of its bioactive constituents. The plant is a shrub commonly used in herbal medicine and could easily be found along the open forest trails. The roots of the collected sample were consecutively extracted with petroleum-ether, chloroform and methanol followed by separation of the chloroform fraction by column chromatography and preparative thin-layer chromatography. In this study we reported the isolation of an aristolactam, Ariskanin-A with a toxicity value of LC50 <200 ppm in Brine-Shrimp Lethality Bioassay based on spectroscopic data and comparison with literature.